2011
DOI: 10.1111/j.1751-7176.2011.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Novel Angiotensin II Receptor Blocker Azilsartan Medoxomil vs Valsartan by Ambulatory Blood Pressure Monitoring

Abstract: Azilsartan medoxomil (AZL-M) is a unique angiotensin II receptor blocker (ARB) under development for the treatment of hypertension. To compare this ARB with another in the class, the authors studied the effects of AZL-M and valsartan (VAL) in 984 patients with primary hypertension in a randomized, double-blind, multicenter study using ambulatory and clinic blood pressure (BP) measurements. The primary end point was change from baseline in 24-hour mean ambulatory systolic BP following 24 weeks of treatment. Hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 24 publications
7
102
0
10
Order By: Relevance
“…32,33 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP. [34][35][36] Given the close structural relationship between azilsartan and candesartan, head to head studies comparing the BP effects of these two drugs are of particular interest. 37 In the present study, we have observed that both Azilsartan (40mg once daily) and Telmisartan (40mg once daily) are effective agents in reducing both systolic and diastolic BP throughout the study period when measured at the baseline with 1 st 2 nd 3 rd 4 th and 5 th week in grade I-II essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP. [34][35][36] Given the close structural relationship between azilsartan and candesartan, head to head studies comparing the BP effects of these two drugs are of particular interest. 37 In the present study, we have observed that both Azilsartan (40mg once daily) and Telmisartan (40mg once daily) are effective agents in reducing both systolic and diastolic BP throughout the study period when measured at the baseline with 1 st 2 nd 3 rd 4 th and 5 th week in grade I-II essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP. [28][29][30] Given the close structural relationship between azilsartan and candesartan, head to head studies comparing the BP effects of these two drugs are of particular interest. Azilsartan 40-80mg per day lowered systolic and diastolic BP significantly more than candesartan cilexetil (12mg).…”
Section: Discussionmentioning
confidence: 99%
“…Оба компонента доказали свою эффектив-ность в многочисленных исследованиях. Так, в иссле-довании Sica D, et al [11] было показано, что азилсар-тан в дозе 40 и 80 мг/сут. сильнее снижает суточное систолическое артериальное давление (САД) и диа-столическое артериальное давление (ДАД), чем вал-сартан в максимальной дозе 320 мг.…”
Section: возможности комбинации азилсартана медоксомила и хлорталидонunclassified